Flexural Behavior of Corroded Reinforced Recycled Aggregate Concrete Beams - Taoping Ye; Wanlin Cao; Yixuan Zhang; Zhengwen Yang (Advances in Materials Science and Engineering)
Recycling concrete not only reduces the use of virgin aggregate but also decreases the pressure on landfills. As a result, recycled coarse aggregate (RCA) is extensively recommended for new construction projects. However, the flexural behavior of corroded reinforced recycled aggregate concrete (RAC) beams is uncertain. The experimental research presented in this paper was performed to investigate the flexural behavior of corroded reinforced RAC beams compared to that of corroded reinforced natural aggregate concrete (NAC) beams and consequently explore the possibility of using RAC beams in corrosive environments. Four different percentages of RCA in total mass of coarse aggregate in concrete mixtures (0%, 33%, 66%, and 100%) and two different concrete strengths (C30, C60) were the governing parameters. The electrochemical method was adopted to accelerate steel corrosion. Full-scale tests were performed on eight simply supported beams until the failure load was reached. Comparison of load-deflection behavior, crack patterns, failure modes, ductility, and ultimate flexural capacity of corroded reinforced NAC and RAC beams was made based on the experimental results obtained. The comparison results show that the flexural behavior of corroded reinforced RAC beams with an appropriate percentage of RCA is satisfactory compared to the behavior of NAC beams.